A Single Amino Acid Residue Defines the Difference in Ovalicin Sensitivity between Type I and II Methionine Aminopeptidases - Brdlik, Cathleen M. (2003)
TNP-470, the first anti-angiogenic small molecule to enter clinical trials, targets methionine aminopepti-dase-2 (MetAP-2), a metalloprotease that cleaves the N-terminal methionine of proteins. Previously, biochemical binding, in vivo yeast studies, and structural studies of human methionine aminopeptidase-2 bound to TNP-470 and its analogs fumagillin and ovalicin revealed that these compounds exhibit specificity for MetAP-2 over its family member MetAP-1. To further elucidate the nature of this specificity, we developed a yeast-based screen for human MetAP-2 mutations that confer ovalicin resistance. Of the three resistant alleles, A362T appeared in the majority of clones and was found to be the most resistant to the ovalicin class of inhibitors. Alignment of human MetAP-2 with human MetAP-1, which is naturally ovalicin-resistant, revealed that the analogous residue in MetAP-1 is also a threonine. Mutation of this residue to alanine resulted in an ovalicin-sensitive MetAP-1 allele, demonstrating that an alanine at this position is critical for inhibition by ovalicin. These results provide a molecular explanation for the specificity exhibited by this class of anti-angiogenic agents for MetAP-2 over MetAP-1 and may prove useful in the development of additional MetAP-2-specific therapeutic agents.